Biossorção de corantes alimentícios utilizando um subproduto da indústria cervejeira - Sartori, Lidiane (2017)
The agroindustrial byproducts, like the residual biomass of beer manufacturing, normally no possess market value, being an liability environmental to the food industries. Your use with biossorvent has being searched in the last years. Already the presence in the food colorings in efluents, even in small quantities, when not properly treated significantly affect the environmente, principaly to solubility on water and coloring. Thus, this study have with objective to develop a absorbent from encapsulation of teh residual biomass from beer manufacturating in order to apply in removal food colorings presents on water promoving a survival to this industrial subproduct before to final destination, and presenting an alternative to the effluents with this substances. In this study, this subproduct was encapsulated in calcium alginate and used on biossorption of Tartrazine Yellow and Brilhant Blue colorings. The capsules has caracterized about your phisical and morfological caracteristics, chemistry compose and funcional groups. After this, was determinated the best pH condition for the colorings biossorptio, was observed that in acid medium the biosorption capacity was best. In this condition were built equilibrium curves, where observed biossorption capacities was 298.4 e 548.5 mg.g-1 to Tartrazine Yellow and Brilhant Blue respectively. The biossorption termodinamic suggest of the colorings biosorptionTartrazine Yellow was exothermic and suggest of the interaction to the biossorvent and the colorings are due the hydrogen bonds. The biosorption thermodynamics of the Brilliant Blue dye proved a probable change of adsorption mechanisms with the increase in temperature. Posteriorly, were done biosorption assays in fixe bed, was avaliated the flw rate effect on the rupture curve to the two colorings. To the both cases the flow rate increment has to the bed saturated more rapidly, being observed a drastic reduction of the capacity of adsorption of the bed, when compared to the values predicted by the isotherms. However, despite to the diferent comportment observed about the colorings, can conclud of the biosorvent produced to capsules of residual biomass beer manufacturating presents potencial to the remove the colorings present in the food industrial effluents.